Silver Micro-Nanoparticles Properties, Synthesis, Characterization, and Applications - Kumar, Samir; Kumar, Prabhat; Shakher Pathak, Chandra (IntechOpen, 2021)
This book describes the different methodologies for producing and synthesizing silver nanoparticles (AgNPs) of various shapes and sizes. It also provides an in-depth understanding of the new methods for characterizing and modifying the properties of AgNPs as well as their properties and applications in various fields. This book is a useful resource for a wide range of readers, including scientists, engineers, doctoral and postdoctoral fellows, and scientific professionals working in specialized fields such as medicine, nanotechnology, spectroscopy, analytical chemistry diagnostics, and plasmonics.